PAI Teacher Competencies In The Era Of Digitalization - Muhammad Shafi'i (Jurnal Pendidikan LLDIKTI Wilayah 1 (JUDIK), 2024)
The era of digitalization has changed the educational landscape, requiring Islamic Religious Education (PAI) teachers to acquire broader competencies in information and communication technology (ICT). This research reveals that PAI teachers need to integrate mastery of technology with strong pedagogical skills to increase learning effectiveness. The development of digital-based teaching materials is crucial, although it still requires improvement in quality and consistency. Apart from that, digital literacy and ethics are an important focus in educating students to use technology responsibly. Support from the government, educational institutions and the community is needed to provide infrastructure and training that supports the development of PAI teacher competencies in this era of digitalization. This transformation is not just about adopting technology, but also about improving the overall quality of education by optimally utilizing the potential of technology.